Pengaruh Profitabilitas, Financial Leverage Dan Dividend Payout Ratio Terhadap Perataan Laba Pada Perusahaan Manufaktur Di BEI Periode 2019-2022 - Fina Puspita Sari; Akhmad Naruli; Miladiah Kusumaningarti (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the partial and simultaneous effects of profitability, financial leverage and dividend payout ratio on earnings smoothing. This type of research is classified as quantitative research. The population are manufacturing companies that focus on the basic and chemical industry sectors listed on the Indonesia Stock Exchange for the 2019-2022 period with a total of 91 companies. The purposive sampling method as a sampling was obtained as many as 72 companies. Using multiple linear regression analysis as analytical techniques assisted with SPSS version 25. The test results from the research show that partially the profitability (as measured by NPM) had no effect on income smoothing, financial leverage (as measured by DPR) had a negative and significant effect on income smoothing and the dividend payout ratio had a significant effect on income smoothing. While simultaneously the variables of profitability, financial leverage and dividend payout ratio have a significant effect on income smoothing.